The essential oil of patchouli, Pogostemon cablin: A review - Beek, Teris A.; Joulain, Daniel (Flavour and fragrance journal, 2018)
The leaves of Pogostemon cablin (Blanco) Benth. (Lamiaceae) are the source of patchouli essential oil, which is – with an annual production of about 1300 tonnes – an important and unique commodity in the fragrance industry. All the literature pertaining to patchouli was critically reviewed with an emphasis on the qualitative and quantitative chemical analysis of the oil but also harvesting, fermentation, drying, distillation, used analytical techniques, sensory aspects including molecules responsible for the odour, adulteration and toxicological aspects, i.e., skin sensitisation, are discussed. In total 72 constituents have been convincingly identified in the oil and another 58 tentatively. The main constituent is the sesquiterpene patchoulol. For this review over 600 papers were consulted and in the supplementary information all patchouli‐related references not relevant enough to be cited in the paper itself are listed. The literature concerning patchouli essential oil, which is derived from the leaves of Pogostemon cablin, was comprehensively reviewed with an emphasis on its chemical constituents and their analysis. Additionally drying and fermentation of leaves, distillation, used analytical techniques, sensory aspects, adulteration and toxicological aspects are discussed.